The effect of ICT investment, ICT governance mechanisms, boards with diverse ICT expertise and ownership structures on firm performance - Marjan, Mohd Noor (2017)
This thesis examined the effects of ICT investment, ICT governance mechanisms, boards with diverse ICT expertise, and ownership structures on firm performance of Malaysian technology sector in the Malaysian Public Listed Companies from 2010 until 2014. This study employed the balanced panel data for a sample of 33 listed companies, with 165 observations. A dynamic model was built and estimation was carried out by using the System Generalized Method of Moments (SGMM). As predicted, ICT investment incurred in the current year displayed a significantly negative impact upon ROE. Even though ICT investment failed to exhibit a significantly positive effect upon firm performance during the initial period of spending, the findings portrayed that ICT spending in current year had the ability to positively influence Tobin’s Q. In fact, ICT investment incurred in the lag of a year showed significantly positive impact on Tobin’s Q. In terms of ICT governance mechanisms, the presence of ICT governance committee had been found to have a significantly negative effect on ROA, ROE, and Tobin’s Q, whereas the presence of ICT senior management showed significantly positive effect upon Tobin’s Q. The boards with ICT industrial experiences displayed a positive effect upon ROA, ROE, and Tobin’s Q, but a significantly negative effect was discovered for boards with ICT professional qualifications on Tobin’s Q. As for ownership structures, managerial ownership exhibited significantly positive effect on Tobin’s Q, but negatively on ROA. Furthermore, the government and foreign ownerships were found to have significantly positive effect on ROA. Hence, the findings from this study are indeed beneficial not only for all stakeholders, including policymakers, regulators, and academics; but also for board of company and management level in ascertaining that their ICT implementation is properly governed under appropriate ICT standards.